Agrarian change and gender relations the case of Batang Ai Resettlement scheme, Sarawak : A brief summary - Hew, Cheng Sim (Pelanduk Publications, 1995)
The aim of the study was to examine how gender relations amongst the Iban had been affected by agrarian changes in Batang Ai. The agrarian changes in Batang Ai have largely been the result of the siting of a hydroelectric dam project in the area. This meant a transfer of subsistence hill paddy farmers to a resettlement scheme where cash crops were cultivated on a plantation basis. Cash compensations were paid to the settlers for the loss of their land, crops and other immovable properties which were inundated.